O lúdico no ensino da matemática: o nim, o tangram e os pentaminós como ferramentas de aprendizagem. - Ferreira, Antonio Erivan Bezerra (2019)
The main objective of this work is to present play activities as a resource to improve the learning of Mathematics, seeking to establish the relationship between the game, teaching and learning new mathematical knowledge. We try to highlight the pedagogical role of games when exploring and applying mathematical concepts through the elaboration of strategies; and to show that by using games in Mathematics teaching, we can improve learning, stimulate concentration, make the learner more involved, thus making it possible to develop skills in the individual as well as make him an ally in the acquisition of mathematical knowledge. We also show that, when using games in Mathematics teaching, the student becomes motivated, favoring the interrelation and causing the learner to take the lead in the learning process. Finally, we try to show the mathematical strategy that leads to the victory of the game Nim in two versions, one using the Algorithm of the division and another using the system of binary numbering.